Magnetic Purification of Curcumin from Curcuma longa Rhizome by Novel Naked Maghemite Nanoparticles - Magro, Massimiliano; Campos, Rene [UNESP]; Baratella, Davide; Ferreira, Maria Izabela [UNESP]; Bonaiuto, Emanuela; Corraducci, Vittorino; Uliana, Maira Rodrigues [UNESP]; Pereira Lima, Giuseppina Pace [UNESP]; Santagata, Silvia; Sambo, Paolo; Vianello, Fabio (Amer Chemical Soc, 2015)
Naked maghemite nanoparticles, namely, surface active maghemite nanoparticles (SAMNs), characterized by a diameter of about 10 nm, possessing peculiar colloidal stability, surface chemistry, and superparamagnetism, present fundamental requisites for the development of effective magnetic purification processes for biomolecules in complex matrices. Polyphenolic molecules presenting functionalities with different proclivities toward iron chelation were studied as probes for testing SAMN suitability for magnetic purification. Thus, the binding efficiency and reversibility on SAMNs of phenolic compounds of interest in the pharmaceutical and food industries, namely, catechin, tyrosine, hydroxytyrosine, ferulic acid, coumaric acid, rosmarinic acid, naringenin, curcumin, and cyanidin-3-glucoside, were evaluated. Curcumin emerged as an elective compound, suitable for magnetic purification by SAMNs from complex matrices. A combination of curcumin, demethoxycurcumin, and bis-demethoxycurcumin was recovered by a single magnetic purification step from extracts of Curcuma longa rhizomes, with a purity >98% and a purification yield of 45%, curcumin being >80% of the total purified curcuminoids.
Keywords: magnetic purification; curcumin; Curcuma longa; curcuminoids; magnetic nanoparticles; polyphenols